Religion and Politics: a reflection on Buckley's legacy and the continuing debate (Journal of the Association for the Study of Australian Literature, 2010)
Vincent Buckley was not only an outstanding poet and literary critic but also a very influential religious thinker and inspirer. This paper discusses Buckley's attitudes to the relation of religion and politics in the context of his complex religious views and his strong political attitudes. It seeks to throw light on the reasons why he was often perceived as a man of the right, though this was not his self-perception and was at odds with much that he thought. The paper then enters directly into some central issues in the complex question of how religion should relate to politics.